KERUKUNAN UMAT BERAGAMA SEBAGAI WUJUD IMPLEMENTASI TOLERANSI - Jaya Dewata, Angga Maulana; Bagaskara, Ganang Pratama; Muttaqin, Dzikrul; Mushlihuddin Salam, Akhmad; Fauzan, Abdul Rahman; Khasanah, Uswatun; Sadari, Sadari (Moderation | Journal of Islamic Studies Review, 2025)
Religious harmony is a fundamental element in maintaining social stability and national unity, especially in a country with religious diversity like Indonesia. This study employs the library research method, analyzing various written sources such as books, scientific journals, research reports, and relevant official documents. A descriptive-qualitative approach is used to explore the supporting and inhibiting factors of religious harmony and examine the implementation of tolerance in society. The study's findings indicate that several factors contribute to religious harmony in Indonesia, including local wisdom values, the role of the government and religious institutions, multicultural education, and strong social interactions. However, several obstacles hinder religious harmony, such as intolerance and radicalism, the spread of religious-based hoaxes, social inequality, and the lack of interfaith dialogue. According to the Religious Harmony Index (Indeks Kerukunan Umat Beragama), Indonesia generally maintains a good level of religious harmony, yet challenges persist in certain regions. This study emphasizes the need for synergy between the government, religious leaders, academics, and society to strengthen religious moderation and prevent potential conflicts. Strategies such as improving digital literacy, strengthening interfaith dialogue, and ensuring social welfare equity must be continuously pursued to maintain interreligious harmony. With an inclusive and participatory approach, Indonesia is expected to remain a country that upholds the values of tolerance in religious life.